Where Did the Women Go? Gender Inequalities in Ecuador's Ethno-Politics. - Picq, Manuela Lavinas (Social Development Issues (Follmer Group), 2014)
Women have long been at the forefront of Indigenous struggles. Their historical protagonism, however, did not translate into political leadership. As Indigenous movements became institutionalized in the 1990s, most women were left behind. Today, ethnopolitics are marked by acute gender inequality, with few women in power. Indigenous women's rights are fundamental tenets to the realization of individual and collective human rights, and as such they are inextricable from democratic practice. In Latin America, the political participation of Indigenous women is a key barometer of democracy. This case study takes an intersectional approach to explore the receding presence of women in Ecuador's Indigenous movement. Gender inequalities reveal the permanence of discriminatory practices within ethno-politics, yet they also signal the lasting influence of external forces.